Collateralized Transactions : Key Considerations for Public Lenders and Borrowers. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2020)
In a response to a request from the G20 IFA Working Group, this note provides a framework for public lenders and borrowers to assess collateralized financing practices from a development perspective. The work of the IMF and World Bank suggests that the availability of collateralized financing can be beneficial to a developing country borrower under a range of circumstances, but also points to pitfalls.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet